2017
DOI: 10.5455/javar.2017.d227
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and identification of subclinical mastitis in cows at BLRI Regional Station, Sirajganj, Bangladesh

Abstract: Objective:The study was conducted to assess the prevalence of subclinical mastitis in dairy cows at Baghabari milk shed area of Sirajganj and Pabna districts in Bangladesh. Materials and methods: A total of 300 milk samples were collected from crossbred dairy cows, and the milk samples were subjected for using California Mastitis Test (CMT). Besides, data related to farm management were taken from 60 farmers through direct interviews. The CMT was compared with White Slide Test (WST) and Surf Field Mastitis Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…As shown in Tables 1 & 3, it was found that the rate of SCM among milk samples by WST revealed an incidence rate of 49% at the quarter level. Nearly similar results of SCM by +ve WST were obtained by Shahid et al (2011); Kabir et al (2017); while lower incidences were obtained by Iqbal et al (2004); Zahid (2004); Barua et al (2014).…”
Section: Discussionsupporting
confidence: 71%
“…As shown in Tables 1 & 3, it was found that the rate of SCM among milk samples by WST revealed an incidence rate of 49% at the quarter level. Nearly similar results of SCM by +ve WST were obtained by Shahid et al (2011); Kabir et al (2017); while lower incidences were obtained by Iqbal et al (2004); Zahid (2004); Barua et al (2014).…”
Section: Discussionsupporting
confidence: 71%
“…However, the prevalence of SCM at the individual cow level was 67.9%, which has consistent and discrepancies with the study reporting prevalence in Bangladesh and around the globe. The estimated prevalence is higher than the reported prevalence of SCM in different district of Bangladesh including Sirajganj, Rajshahi, Chattogram and Barisal [8,15,17,31]again the reported SCM prevalence is lower than the prevalence of SCM calculated in Nigeria (85.3%) [32], Uganda (86.2%) [33] and Vietnam (88.6%) [34]. However, the estimated SCM prevalence is higher than the study conducted inKenya [35], Ethiopia [36], New South Wales of Australia [37], Rwanda [19]and Uruguay [38].…”
Section: Prevalence Of Scmmentioning
confidence: 54%
“…On the other hand, BMT could be used as an inexpensive test to assess the SCM of animals, as reported by Sargeant et al [22] on CMT. In another study, we found the CMT as an effective test kit for assessing SCM [13]. However, Sarker et al [23] and Sumon et al [17] found only 20.2% and 25% prevalence of SCM in dairy cows, respectively.…”
Section: Resultsmentioning
confidence: 94%